Development of bamboo- (Bambusa bambos) based bio-fence to protect field crops: Insights from a study in India's Bundelkhand region - Kumar, Dinesh; Yadav, Ram Swaroop; Kadam, Darshan Manikrao; Ahirwar, Lakhan Lal; Dohare, Anil Kumar; Singh, Gautam (Frontiers in Ecology and Evolution, 2022)
Crop damage due to stray/wild animals is a difficult to control worldwide problem that is leading to unrest among farmers. In the Bundelkhand region of India, this problem is more severe due to 'Anna Pratha’ i.e. letting loose animals for open grazing. The crop protective measures (barbed wire fencing, conventional fencing, etc.) followed by farmers are not fully effective and also require periodical maintenance involving additional costs and manpower. This necessitates the requirement to evolve a cost-effective and long-term solution to minimize the problem. Therefore, the current study was planned, for the first time, to evaluate the potential of thorny bamboo (Bambusa bambos) as a bio-fence creating deterrence to stray/wild animals at the research farm of ICAR – IISWC RC, Datia, Madhya Pradesh, India. After 21 months of planting, bamboo plants attained the maximum plant height up to 4.47 m with highest clump spread diameter of 30.50 cm. However, the growth of bamboo bio-fence to be effective depends upon the edaphic and management conditions. The findings revealed that planting bamboo at a spacing of 80.00 cm in the continuous trench can be an effective bio-fence to avoid man–animal conflict. Huge crop losses were reported before the establishment of bio-fence. During the year 2021-22 (when bamboo plants turned into closely-spaced thicket, making a bio-fence), only two incidents of animals’ invasion were reported with no crop damage. The initial cost to develop bamboo bio-fence was estimated US$ 76.52 for a length of 100 meters. Thus, the present study suggests bamboo bio-fencing an economic and effective crop protection measure against wild/stray animals’ damage.